Pharmacokinetics of Oral Nirmatrelvir/Ritonavir, a Protease Inhibitor for Treatment of COVID‐19, in Subjects With Renal Impairment. Issue 4 (5th July 2022) - Toussi, Sima S.; Neutel, Joel Michael; Navarro, Jesus; Preston, Richard Alfred; Shi, Haihong; Kavetska, Olga; LaBadie, Robert R.; Binks, Michael; Chan, Phylinda L.S.; Demers, Neil; Corrigan, Brian; Damle, Bharat
Abstract : Nirmatrelvir coadministered with ritonavir is highly efficacious in reducing the risk of coronavirus disease 2019 (COVID‐19) adverse outcomes among patients at increased risk of progression to severe disease, including patients with chronic kidney disease. Because nirmatrelvir is eliminated by the kidneys when given with ritonavir, this phase I study evaluated the effects of renal impairment on pharmacokinetics, safety, and tolerability of nirmatrelvir/ritonavir. Participants with normal renal function ( n  = 10) or mild, moderate, or severe renal impairment ( n  = 8 each) were administered a single 100‐mg nirmatrelvir dose with 100 mg ritonavir given 12 hours before, together with and 12 and 24 hours after the nirmatrelvir dose. Systemic nirmatrelvir exposure increased with increasing renal impairment, with mild, moderate, and severe renal impairment groups having respective adjusted geometric mean ratio areas under the plasma concentration‐time profile from time 0 extrapolated to infinite time of 124%, 187%, and 304% vs. the normal renal function group. Corresponding ratios for maximum plasma concentration were 130%, 138%, and 148%. Apparent clearance was positively correlated with estimated glomerular filtration rate, and geometric mean renal clearance values were particularly lower for the moderate (47% decrease) and severe (80% decrease) renal impairment groups vs. the normal renal function group. Nirmatrelvir/ritonavir exhibited an acceptable safety profile; treatment‐related adverse events were mild in severity, and there were no significant findings regarding laboratory measurements, vital signs, or electrocardiogram assessments. These findings led to a dose reduction recommendation for nirmatrelvir/ritonavir in patients with moderate renal impairment (150/100 mg nirmatrelvir/ritonavir instead of 300/100 mg twice daily for 5 days). NCT04909853.